The Use of Chemicals with Specific Mode of Action in an Integrated Control Program on Eggplant for the Greenhouse Whitefly, Triαleurodes vαporαriorum - Abdalla, Safel Dawla; Michelakis, S. (ENTOMOLOGIA HELLENICA, 1998)
In the unheated plastic greenhouses of Crete, the control of the greenhouse whitefly Trialeurodes vaporariorum Westwood using chemicals is usually needed during winter time. The systemic insecticide Vydate when applied as soil granules at the highest dose (2g/plant), gave protection for young eggplants against whitefly for a period of 5 weeks. Experiment with different chemicals showed that the new insect growth regulator Nomolt, is fairly effective in controlling the greenhouse whitefly when used in combination with Actellic. It gave equally good results when compared with a mixture of Applaud and Actellic.